A wide temperature range self-lubricating material and preparation method thereof

By synthesizing MoS2/Ag nanocomposite lubricant in a porous metal cermet matrix, the problem of mutual constraints on the mechanical strength and lubricating performance of solid self-lubricating materials in a wide temperature range is solved, and the low friction and low wear effect in a wide temperature range is achieved.

CN114774916BActive Publication Date: 2025-02-25WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210295622.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-24
Publication Date
2025-02-25
Estimated Expiration
2042-03-24

AI Technical Summary

Technical Problem

In the prior art, the mechanical strength and lubricating properties of solid self-lubricating materials are mutually restricted, making it difficult to maintain low friction and low wear in a wide temperature range.

Method used

The porous cermet matrix is ​​used as a carrier, and two lubricants MoS2 and Ag are synthesized in the pores of the matrix through vacuum pressure immersion and hydrothermal reaction methods to form MoS2/Ag nanocomposite lubricants to achieve a synergistic lubricant.

Benefits of technology

Low friction and low wear within the range of room temperature to 600°C, the crush strength is greater than 800MPa, the microhardness is greater than 1000HV, the friction coefficient is between 0.16 and 0.32, and the wear rate is as low as 10-7mm3/N·m.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114774916B_ABST
    Figure CN114774916B_ABST
Patent Text Reader

Abstract

The present invention discloses a wide temperature range self-lubricating material and a preparation method thereof, comprising the following steps: (1) adding a precursor solution of MoS2 to the pores of a porous metal ceramic matrix by vacuum pressure impregnation to obtain a matrix A; (2) placing the matrix A and the precursor solution of MoS2 in a reactor for hydrothermal reaction to generate a matrix B, taking out the matrix B for cleaning and drying to obtain a matrix C; (3) adding a precursor solution of Ag to the pores of the matrix C by vacuum pressure impregnation to obtain a matrix D; (4) placing the matrix D and the precursor solution of Ag in a reactor for hydrothermal reaction to generate a matrix E, taking out the matrix E for cleaning and drying to obtain a wide temperature range self-lubricating material. In the present invention, an impregnation and two-step hydrothermal synthesis method are adopted to successively synthesize two nano-lubricants, MoS2 and Ag, in the pores of the matrix, which have a synergistic lubrication effect in a wide temperature range, and realize low friction and low wear of the material in a wide temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid self-lubricating materials, and in particular to a wide temperature range self-lubricating material and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of nanotechnology, nanomaterials have been widely used in the field of tribology due to their small size, large specific surface area, high surface activity and other advantages. In the form of nanoparticles or nanofilms, they have special friction reduction and high load capacity in lubrication and tribology. Nanolubricants have better tribological properties than ordinary lubricants due to their small scale effect.

[0003] Traditionally, solid self-lubricating materials are prepared by sintering a mixture of lubricant and matrix powder. During the preparation of self-lubricating materials by this method, some lubricants will fail and lose their lubricity due to the high sintering temperature. At the same time, the distribution of solid lubricants in the matrix will reduce the strength and hardness of the material, making it difficult to take into account both self-lubricating properties and mechanical properties.

[0004] The invention patent No. 200410060662.4, "A high-temperature self-compensating lubricating wear-resistant material and its preparation method", uses powder metallurgy to prepare a metal ceramic sintered body material with through-pore structure characteristics. This material has high mechanical strength, good wear resistance and through-pore structure characteristics, and is an ideal matrix material for self-lubricating composite materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art, provide a wide temperature range high-strength self-lubricating material and a preparation method thereof, and solve the technical problem of the mutual restriction between the mechanical strength and lubrication performance of the self-lubricating material in the prior art.

[0006] In order to achieve the above technical purpose, the technical solution of the preparation method of the present invention is:

[0007] The following steps are involved:

[0008] (1) adding a precursor solution of MoS2 into the pores of a porous metal ceramic matrix by vacuum pressure impregnation to obtain a matrix A;

[0009] (2) placing the matrix A and the precursor solution of MoS2 into a reaction kettle for hydrothermal reaction to generate the matrix B, taking out the matrix B, cleaning it, and drying it to obtain the matrix C;

[0010] (3) adding the Ag precursor solution into the pores of the substrate C by vacuum pressure impregnation to obtain the substrate D;

[0011] (4) Putting the matrix D and the Ag precursor solution into a reactor for hydrothermal reaction to generate the matrix E. Taking out the matrix E, cleaning it, and drying it to obtain a wide temperature range self-lubricating material.

[0012] Furthermore, in step (1), the precursor solution of MoS2 is obtained by completely dissolving sodium molybdate and thiourea in deionized water, and the mass ratio of sodium molybdate, thiourea and deionized water is (2.9-8.2): (4.1-10.3):100.

[0013] Furthermore, in step (1), the porous metal ceramic substrate is first pretreated and then impregnated; the pretreatment is to first grind and polish the surface of the porous metal ceramic substrate, then ultrasonically treat it with 10wt% to 20wt% dilute hydrochloric acid for 20 to 40 minutes, then ultrasonically treat it with anhydrous ethanol for 20 to 40 minutes, and finally dry it at 60 to 80°C for standby use.

[0014] Furthermore, in step (1) and step (3), the vacuum pressure impregnation is first carried out in an environment with a vacuum degree of 0.08 to 0.1 MPa for 20 to 40 minutes, and then high-pressure nitrogen is introduced, and the pressure is controlled at 0.02 MPa to 0.05 MPa and maintained for 30 to 60 minutes.

[0015] Furthermore, in step (2), the hydrothermal reaction is carried out at 180-220° C. for 22-26 hours.

[0016] Furthermore, in step (2), after the substrate B is taken out, it is first polished with sandpaper and then ultrasonically cleaned with anhydrous ethanol for 5 to 15 minutes until the pores of the substrate are exposed, and then dried to obtain a substrate C.

[0017] Furthermore, in step (3), the Ag precursor solution is obtained by dissolving silver nitrate and polyvinyl pyrrolidone in a solvent, and the mass ratio of silver nitrate, polyvinyl pyrrolidone and solvent is (1.7-8.5):(1.7-12.75):100.

[0018] Furthermore, in the Ag precursor solution, the solvent is a mixture of water, anhydrous ethanol and pyridine in a volume ratio of (7-4): (2-5): (0-1).

[0019] Furthermore, in step (4), the hydrothermal reaction is carried out at 170-190° C. for 22-26 hours.

[0020] The wide temperature range self-lubricating material is prepared by the preparation method as described above.

[0021] Compared with the prior art, the beneficial effects of the present invention include:

[0022] 1. The porous metal ceramic matrix of the present invention has sweat gland-like micropores. The two lubricants, MoS2 and Ag, are synthesized in the matrix pores in succession by a two-step hydrothermal synthesis method of impregnation. The composite of the two lubricants has a synergistic lubrication effect, which ensures that the material has a wide temperature range of use. At room temperature, MoS2 and Ag play a lubricating and friction-reducing role together. At medium and high temperatures, MoS2, Ag and the matrix undergo a tribochemical reaction to generate high-temperature lubricants such as silver molybdate, which play a major lubricating role. The self-lubricating material prepared by the present invention has a crushing strength greater than 800MPa and a microhardness greater than 1000HV. In the range of room temperature to 600℃, the friction coefficient is between 0.16 and 0.32, and the wear rate is as low as 10 -7 mm 3 / N·m order of magnitude, achieving low friction and low wear in a wide temperature range.

[0023] 2. Two hydrothermal reactions are used to synthesize the composite lubricating phase in the pores of the matrix. The equipment required is simple and the operation is simple and easy. Two hydrothermal reactions ensure that the lubricant enters the matrix deeply, fills densely, and does not affect the matrix skeleton, with high strength and good wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The images of the cross section of the lubricating layer of the wide temperature range self-lubricating material prepared by the present invention and the element distribution diagrams of Mo, S (MoS2) and silver, among which: (a) is the SEM image of the cross section of the composite material, (b) is the EDS distribution diagram of the cross section elements, (c) is the Fe element distribution diagram of the cross section, (d) is the S element distribution diagram of the cross section, (e) is the Mo element distribution diagram of the cross section, and (f) is the Ag element distribution diagram of the cross section.

[0025] Figure 2 SEM morphology, cross-sectional pore morphology and micro-area elemental composition analysis of hydrothermally synthesized MoS2 and Ag powders, where: (a) is the SEM image of synthesized MoS2 powder, (b) is the SEM image of synthesized Ag powder, and (c) is the cross-sectional pore morphology and micro-area elemental composition analysis.

[0026] Figure 3 Friction coefficient change curves of porous metal-ceramic matrix and Ag-MoS2 / porous metal-ceramic composites at room temperature and 600℃. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0028] The present invention uses a simpler and lower-cost method to prepare a self-lubricating material by adding a nano-composite lubricant to a porous metal ceramic matrix with sweat gland-like micropores to meet the requirements of use in a wide temperature range. The preparation method of the wide temperature range self-lubricating material of the present invention mainly includes the following steps:

[0029] (1) dissolving sodium molybdate and thiourea powder in deionized water, and stirring them thoroughly to completely dissolve them to obtain a MoS2 precursor solution; when preparing the precursor solution, the mass ratio of sodium molybdate: thiourea: deionized water is: 2.9-8.2: 4.1-10.3: 100;

[0030] (2) pre-treating a porous metal ceramic substrate with sweat gland-like micropores (prepared according to ZL200410060662.4), and adding the precursor solution obtained above into the pores of the substrate by vacuum pressure impregnation;

[0031] The specific method for pretreatment of the porous metal ceramic substrate is as follows: first, the surface of the substrate is ground and polished, then the porous metal ceramic substrate is ultrasonically treated with (mass fraction 10% to 20%) dilute hydrochloric acid for 20 to 40 minutes, then ultrasonically treated with anhydrous ethanol for 20 to 40 minutes, and then dried in an electric furnace at 60 to 80° C. for standby use;

[0032] The specific operation of vacuum pressure impregnation is as follows: first, the substrate is placed in a beaker and placed in a vacuum pressure impregnation box, and vacuum is drawn, and the vacuum degree is maintained at 0.08-0.1 MPa. The solution is sucked into the beaker in the vacuum pressure impregnation box from an inlet of the vacuum pressure impregnation box, and maintained for 20-40 minutes. Then, high-pressure nitrogen is introduced, and the pressure is controlled at 0.02 MPa-0.05 MPa, and maintained for 30-60 minutes.

[0033] (3) The impregnated substrate and solution are transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 180-220°C for 22-26 hours. After naturally cooling to room temperature, the substrate is taken out to remove the product on the surface, cleaned and dried to expose the surface pores.

[0034] The method for removing the generated substances on the substrate surface is to first gently polish it with sandpaper, and then ultrasonically clean it with anhydrous ethanol for 5 to 15 minutes until the pores of the substrate are exposed.

[0035] (4) dissolving silver nitrate and polyvinyl pyrrolidone in a mixed solution of water, anhydrous ethanol and pyridine, and stirring them thoroughly to completely dissolve them, thereby obtaining a Ag precursor solution;

[0036] The volume ratio of water, anhydrous ethanol and pyridine in the mixed solution is 7-4:2-5:1. The mass ratio of silver nitrate:polyvinyl pyrrolidone:mixed solution is 1.7-8.5:1.7-12.75:100.

[0037] (5) adding the Ag precursor solution prepared in step (4) into the pores of the substrate after cleaning and drying in step (3) by vacuum pressure impregnation, and the specific operation of vacuum pressure impregnation is the same as step 2;

[0038] (6) The impregnated substrate and solution are transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 170-190°C for 22-26 hours. After naturally cooling to room temperature, the substrate is repeatedly washed with deionized water and anhydrous ethanol and then dried to clean the excess material on the surface of the substrate, and then polished to obtain a wide temperature range self-lubricating material.

[0039] The wide temperature range self-lubricating material obtained by the present invention is a composite of a porous metal ceramic matrix and two lubricants, nano MoS2 / Ag. The porous metal ceramic matrix has sweat gland-like micropores, and the precursor solution is fully allowed to enter the micropores through vacuum pressure impregnation; by using two hydrothermal reactions, a specific precursor solution concentration (such as the precursor solution concentration of MoS2 cannot be too low or too high, if it is too low, not enough MoS2 can be generated in the pores, and not enough silver molybdate can be generated during high-temperature friction; if it is too high, not enough gaps are retained in the pores, the amount of Ag precursor solution entering is small or even sealed outside the pores, and not enough Ag can be generated, which in turn affects the generation of high-temperature lubricating phase silver molybdate) is ensured to synthesize MoS2 and Ag nanoparticles in situ in these interconnected and orderly micropores, forming a lubricating layer in which MoS2 and Ag phases are mutually doped and distributed in the pores. Since MoS2 and Ag are filled in the micropores of the matrix, the soft metal Ag will precipitate to the friction surface along the pore channels of the matrix under the action of friction heat-stress and extrusion. During the friction process, a lubricating film of MoS2, Ag and their friction reaction products will be formed, achieving low friction and low wear of the material.

[0040] Example 1

[0041] A method for preparing a wide temperature range self-lubricating material mainly comprises the following steps:

[0042] (1) Weigh 5.808 g of sodium molybdate and 8.208 g of thiourea powder and dissolve them in 120 ml of deionized water, and stir them thoroughly to completely dissolve them to obtain a MoS2 precursor solution;

[0043] (2) The metal ceramic substrate with sweat gland-like micropores is pretreated by first grinding and polishing the surface of the substrate, then ultrasonically treating the porous metal ceramic substrate with 10% dilute hydrochloric acid for 30 minutes, and then ultrasonically treating it with anhydrous ethanol for 30 minutes, and drying it in an electric furnace at 80°C; then placing it in a beaker and placing it in a vacuum pressure impregnation box, evacuating the box, and maintaining the vacuum degree at 0.1 MPa. The solution is sucked into the beaker in the vacuum pressure impregnation box from an inlet of the vacuum pressure impregnation box, and maintained for 30 minutes. Then, high-pressure nitrogen is introduced, and the pressure is controlled at 0.03 MPa and maintained for 30 minutes.

[0044] (3) The impregnated substrate and solution were transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 220°C for 24 hours. After naturally cooling to room temperature, the substrate was taken out, and the surface product was gently polished with sandpaper, then ultrasonically cleaned with anhydrous ethanol for 5 minutes and dried.

[0045] (4) Mix 55 ml of ethanol, 55 ml of water and 10 ml of pyridine, dissolve 6.12 g of silver nitrate and 9.18 g of polyvinyl pyrrolidone in the mixed solution of ethanol, water and pyridine, and stir thoroughly to completely dissolve them to obtain a Ag precursor solution;

[0046] (5) adding the Ag precursor solution prepared in step (4) into the pores of the substrate after cleaning and drying in step (3) again by vacuum pressure impregnation, wherein the specific operation of vacuum pressure impregnation is the same as step 2;

[0047] (6) The impregnated substrate and solution are transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 180°C for 24 hours. After naturally cooling to room temperature, the substrate is repeatedly washed with deionized water and anhydrous ethanol and then dried, and the product on the surface of the substrate is polished to obtain a wide temperature range self-lubricating material.

[0048] Example 2

[0049] A method for preparing a wide temperature range self-lubricating material mainly comprises the following steps:

[0050] (1) Weigh 3.485 g of sodium molybdate and 4.925 g of thiourea powder and dissolve them in 120 ml of deionized water, and stir them thoroughly to completely dissolve them to obtain a MoS2 precursor solution;

[0051] (2) The metal ceramic substrate with sweat gland-like micropores is pretreated by first grinding and polishing the surface of the substrate, then ultrasonically treating the porous metal ceramic substrate with 10% dilute hydrochloric acid for 30 minutes, and then ultrasonically treating it with anhydrous ethanol for 30 minutes, and drying it in an electric furnace at 80°C; then placing it in a beaker and placing it in a vacuum pressure impregnation box, evacuating the box, and maintaining the vacuum degree at 0.1 MPa. The solution is sucked into the beaker in the vacuum pressure impregnation box from an inlet of the vacuum pressure impregnation box, and maintained for 30 minutes. Then, high-pressure nitrogen is introduced, and the pressure is controlled at 0.03 MPa and maintained for 30 minutes.

[0052] (3) The impregnated substrate and solution were transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 220°C for 24 hours. After naturally cooling to room temperature, the substrate was taken out, and the surface product was gently polished with sandpaper, then ultrasonically cleaned with anhydrous ethanol for 5 minutes and dried.

[0053] (4) Mix 55 ml of ethanol, 55 ml of water and 10 ml of pyridine, dissolve 8.16 g of silver nitrate and 12.24 g of polyvinyl pyrrolidone in the mixed solution of ethanol and water, and stir thoroughly to completely dissolve them to obtain a Ag precursor solution;

[0054] (5) adding the Ag precursor solution prepared in step (4) into the pores of the substrate after cleaning and drying in step (3) by vacuum pressure impregnation, and the specific operation of vacuum pressure impregnation is the same as step 2;

[0055] (6) The impregnated substrate and solution are transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 180°C for 24 hours. After naturally cooling to room temperature, the substrate is repeatedly washed with deionized water and anhydrous ethanol and then dried, and the product on the surface of the substrate is polished to obtain a wide temperature range self-lubricating material.

[0056] Example 3

[0057] A method for preparing a wide temperature range self-lubricating material mainly comprises the following steps:

[0058] (1) Weigh 8.712 g of sodium molybdate and 12.312 g of thiourea powder and dissolve them in 120 ml of deionized water, and stir them thoroughly to completely dissolve them to obtain a MoS2 precursor solution;

[0059] (2) The metal ceramic substrate with sweat gland-like micropores is pretreated by first grinding and polishing the surface of the substrate, then ultrasonically treating the porous metal ceramic substrate with 10% dilute hydrochloric acid for 30 minutes, and then ultrasonically treating it with anhydrous ethanol for 30 minutes, and drying it in an electric furnace at 80°C; then placing it in a beaker and placing it in a vacuum pressure impregnation box, evacuating the box, and maintaining the vacuum degree at 0.1 MPa. The solution is sucked into the beaker in the vacuum pressure impregnation box from an inlet of the vacuum pressure impregnation box, and maintained for 30 minutes. Then, high-pressure nitrogen is introduced, and the pressure is controlled at 0.03 MPa and maintained for 30 minutes.

[0060] (3) The impregnated substrate and solution were transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 220°C for 24 hours. After naturally cooling to room temperature, the substrate was taken out, and the surface product was gently polished with sandpaper, then ultrasonically cleaned with anhydrous ethanol for 5 minutes and dried.

[0061] (4) Mix 55 ml of ethanol, 55 ml of water and 10 ml of pyridine, dissolve 4.08 g of silver nitrate and 6.12 g of polyvinyl pyrrolidone in the mixed solution of ethanol, water and pyridine, and stir thoroughly to completely dissolve them to obtain a Ag precursor solution;

[0062] (5) adding the Ag precursor solution prepared in step (4) into the pores of the substrate after cleaning and drying in step (3) by vacuum pressure impregnation, and the specific operation of vacuum pressure impregnation is the same as step 2;

[0063] (6) The impregnated substrate and solution are transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 180°C for 24 hours. After naturally cooling to room temperature, the substrate is repeatedly washed with deionized water and anhydrous ethanol and then dried, and the product on the surface of the substrate is polished to obtain a wide temperature range self-lubricating material.

[0064] Example 4

[0065] A method for preparing a wide temperature range self-lubricating material mainly comprises the following steps:

[0066] (1) Weigh 5.808 g of sodium molybdate and 8.208 g of thiourea powder and dissolve them in 120 ml of deionized water, and stir them thoroughly to completely dissolve them to obtain a MoS2 precursor solution;

[0067] (2) The metal ceramic substrate with sweat gland-like micropores is pretreated by first grinding and polishing the surface of the substrate, then ultrasonically treating the porous metal ceramic substrate with 10% dilute hydrochloric acid for 30 minutes, and then ultrasonically treating it with anhydrous ethanol for 30 minutes, and drying it in an electric furnace at 80°C; then placing it in a beaker and placing it in a vacuum pressure impregnation box, evacuating the box, and maintaining the vacuum degree at 0.1 MPa. The solution is sucked into the beaker in the vacuum pressure impregnation box from an inlet of the vacuum pressure impregnation box, and maintained for 30 minutes. Then, high-pressure nitrogen is introduced, and the pressure is controlled at 0.03 MPa and maintained for 30 minutes.

[0068] (3) The impregnated substrate and solution were transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 220°C for 24 hours. After naturally cooling to room temperature, the substrate was taken out, and the surface product was gently polished with sandpaper, then ultrasonically cleaned with anhydrous ethanol for 5 minutes and dried.

[0069] (4) Mix 60 ml of ethanol and 60 ml of water, dissolve 6.12 g of silver nitrate and 9.18 g of polyvinyl pyrrolidone in the mixed solution of ethanol and water, and stir thoroughly to completely dissolve them to obtain a Ag precursor solution;

[0070] (5) adding the Ag precursor solution prepared in step (4) into the pores of the substrate after cleaning and drying in step (3) by vacuum pressure impregnation, and the specific operation of vacuum pressure impregnation is the same as step 2;

[0071] (6) The impregnated substrate and solution are transferred to a high-pressure reactor, sealed and placed in an oven for reaction at 180°C for 24 hours. After naturally cooling to room temperature, the substrate is repeatedly washed with deionized water and anhydrous ethanol and then dried, and the excess material on the surface of the substrate is polished to obtain a wide temperature range self-lubricating material.

[0072] The self-lubricating material prepared in Example 1 of the present invention has a crushing strength of 807.8 MPa and a microhardness of 1040 HV; it has excellent lubrication performance in the temperature range of room temperature to 600°C, see Table 1. Test conditions: load 20N, rotation speed 100r / min (0.23m / s), dual ball is Si3N4 ball (φ10mm), friction time 120min.

[0073] Table 1 Friction coefficient and wear rate of the wide temperature range self-lubricating material of the present invention at different temperatures

[0074] temperature Friction coefficient <![CDATA[Wear rate mm 3 / N·m]]> RT 0.32 <![CDATA[0.4x10 -6 <!-- 5 -->]]> 200℃ 0.21 <![CDATA[0.98x10 -6 ]]> 400℃ 0.16 <![CDATA[1.56x10 -6 ]]> 600℃ 0.22 <![CDATA[1.99x10 -6 ]]>

[0075] As shown in Table 1 above, when the self-lubricating material prepared in Example 1 is ground against Si3N4 ball, the friction coefficient at room temperature is as low as about 0.3, the friction coefficient at 200°C is 0.21, the friction coefficient at 400°C is 0.16, and the friction coefficient at 600°C is as low as about 0.2. It can be seen that the friction coefficient shows a downward trend with the increase of temperature, and the wear rate is as low as 10 -7 mm 3 / N·m order of magnitude (0.4x10 -6 ~1.99x10 -6 mm 3 / N·m), the wear rate tends to increase with the increase of temperature, but is lower than 2.0x10 -6 mm 3 / N·m.

[0076] The image of the cross section of the lubricating layer of the wide temperature range self-lubricating material prepared in Example 1 and the distribution diagram of Mo, S elements (MoS2) and silver elements are shown in FIG. Figure 1 The hydrothermal synthesis powder and cross-section pore morphology SEM and micro-area element composition analysis are shown in Figure 2 As shown. Figure 1 as well as Figure 2 It can be seen that the MoS2 / Ag nanocomposite lubricant was in situ synthesized in the through-network pores of the matrix. The MoS2 is composed of ultra-thin nanosheets similar to potato chips, and the generated nanosilver is in the form of spherical particles.

[0077] By comparing the friction coefficient variation curves of the composite self-lubricating material obtained by the present invention and the porous metal ceramic (pure matrix) at different temperatures (room temperature, 600°C), the results are as follows: Figure 3 As shown, where:

[0078] a: Curve of friction coefficient of porous metal ceramics changing with time at room temperature;

[0079] b: Curve of friction coefficient of porous metal ceramics changing with time at 600°C;

[0080] c: Curve of the change of friction coefficient of the MoS2-Ag / porous metal ceramic composite material prepared in Example 1 of the present invention over time at room temperature;

[0081] d: Curve of the change in friction coefficient of the MoS2-Ag / porous metal ceramic composite material prepared in Example 1 of the present invention at 600°C over time.

[0082] Depend on Figure 3 It can be seen that the friction coefficient of the material of the present invention increases with time at room temperature and 600°C, with little change, and is stable between 0.15 and 0.35 within 120 minutes, with very small fluctuations; while the friction coefficient of the porous metal ceramic matrix shows an increasing trend with time at room temperature (initial value is about 0.55, about 0.91 at 120 minutes), and shows a decreasing trend with time at 600°C (initial value is about 0.75, about 0.68 at 120 minutes), and the overall fluctuation range is relatively large, at 0.55 to 1.0.

[0083] Comparative Example 1

[0084] 3.84 g (24 mmol, the same molar amount as sodium molybdate in Example 1) of MoS2 nanosheets were added to 120 ml of water, and a MoS2 dispersion was prepared by stirring and ultrasonication. After the porous metal ceramic substrate was pretreated, the MoS2 dispersion was added to the pores of the substrate by vacuum pressure impregnation. The other steps were the same as in Example 1.

[0085] Testing of the obtained self-lubricating material revealed large fluctuations in the friction coefficient, especially at room temperature, where the friction coefficient is close to that of the metal ceramic matrix. This is because nano-MoS2 has poor dispersibility in water and is easy to agglomerate. After impregnation, the micropores of the metal ceramic matrix are blocked, leaving only a small amount of agglomerated MoS2 at the micropore openings, making it impossible for MoS2 to exert its excellent lubrication properties at medium and low temperatures.

[0086] Comparative Example 2

[0087] 5.184 g (48 mmol, the same molar amount as silver nitrate in Example 1) of nanosilver was added to 120 ml of water, and a nanosilver dispersion was prepared by stirring and ultrasonication. The nanosilver dispersion was added to the pores of the substrate treated in step (3) by vacuum pressure impregnation. The other steps were the same as in Example 1.

[0088] The self-lubricating material obtained was tested, and the friction coefficient was low at medium and low temperatures, and low at the initial stage at 600°C, but it rose rapidly after a short time. This is because the nanosilver particles have a large specific surface area, high surface energy, and are easy to agglomerate. The dispersion effect in water is very poor, so less Ag can enter the matrix, and high-temperature lubricating phases such as silver molybdate cannot be generated at high temperatures. MoS2 is violently oxidized at 600°C, resulting in a rapid increase in the friction coefficient.

[0089] Comparative Example 3

[0090] The pretreatment process in step (2) is removed, and the MoS2 precursor solution is directly added into the pores of the porous metal ceramic matrix by vacuum pressure impregnation. Other conditions are the same as those in Example 1.

[0091] The self-lubricating material was tested and found that the friction coefficient was low at the beginning of friction, but it fluctuated greatly. After a period ranging from several minutes to more than ten minutes, the friction coefficient slowly increased and could not stabilize. This is mainly because the surface of the self-lubricating material must be polished before the tribological experiment. Since the surface roughness of the metal ceramic matrix is ​​large after sintering, polishing after the hydrothermal reaction will reduce the thickness of the lubricating layer formed by the lubricant generated in situ by the hydrothermal reaction, and the lubricant content will decrease, which leads to this phenomenon. The purpose of pretreatment is to leave a margin for subsequent processing.

[0092] The self-lubricating material of the present invention is prepared by synthesizing MoS2 / Ag nano-composite lubricant in situ in the through pores inside the matrix through two hydrothermal reactions on the basis of a porous metal ceramic matrix. First, a precursor solution of MoS2 is added to the pores of the matrix through vacuum pressure impregnation, and the porous metal ceramic matrix and the solution after impregnation are transferred to a high-pressure reactor for hydrothermal reaction. After the reaction is completed, the material sample is taken out and dried in an oven. Subsequently, a precursor solution of Ag is added to the pores of the above-mentioned sample through vacuum pressure impregnation, and a second hydrothermal reaction is carried out in the high-pressure reactor, thereby synthesizing MoS2 / Ag nano-composite lubricant in situ in the pores. The material sample is taken out and dried in an oven.

[0093] The present invention synthesizes MoS2 / Ag nanocomposite lubricant in a porous ceramic matrix through a secondary hydrothermal reaction, which has a synergistic lubrication effect. At room temperature, MoS2 and Ag jointly play a lubricating and friction-reducing role. At medium and high temperatures, MoS2, Ag and the matrix undergo a tribochemical reaction to generate high-temperature lubricating phases such as silver molybdate to play a lubricating role, thereby achieving excellent self-lubricating properties of the material in a wide temperature range (room temperature to 600°C). The manufacturing process of the present invention is simple and easy, and the prepared material has excellent characteristics of low friction and high wear resistance in a wide temperature range, and has important engineering application value and innovative significance.

[0094] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a wide temperature range self-lubricating material, characterized in that: It consists of the following steps: (1) adding a precursor solution of MoS2 into the pores of a porous metal ceramic matrix by vacuum pressure impregnation to obtain a matrix A, wherein the porous metal ceramic matrix has sweat gland-like micropores; (2) Putting the precursor solution of matrix A and MoS2 into a reactor for hydrothermal reaction to generate matrix B, taking out matrix B, cleaning it and drying it to obtain matrix C. After taking out matrix B, first grind it with sandpaper and then ultrasonically clean it with anhydrous ethanol for 5 to 15 minutes until the pores of the matrix are exposed, and then dry it to obtain matrix C; (3) Adding the Ag precursor solution into the pores of the substrate C by vacuum pressure impregnation to obtain the substrate D; (4) placing the matrix D and the Ag precursor solution into a reactor for hydrothermal reaction to generate the matrix E, taking out the matrix E, cleaning it, and drying it to obtain a wide temperature range self-lubricating material; In step (1), the precursor solution of MoS2 is obtained by completely dissolving sodium molybdate and thiourea in deionized water, and the mass ratio of sodium molybdate, thiourea and deionized water is (2.9-8.2): (4.1-10.3): 100; In step (3), the Ag precursor solution is obtained by dissolving silver nitrate and polyvinyl pyrrolidone in a solvent, and the mass ratio of silver nitrate, polyvinyl pyrrolidone and solvent is (1.7-8.5): (1.7-12.75): 100; In step (1), the porous metal ceramic substrate is first pretreated and then impregnated; the pretreatment is to first grind and polish the surface of the porous metal ceramic substrate, then ultrasonically treat it with 10wt%~20wt% dilute hydrochloric acid for 20~40min, then ultrasonically treat it with anhydrous ethanol for 20~40min, and finally dry it at 60~80℃ for standby use; The self-lubricating material has a crushing strength greater than 800 MPa, a microhardness greater than 1000 HV, a friction coefficient between 0.16 and 0.32 in the range of room temperature to 600°C, and a wear rate as low as 10 -7 mm 3 / N·m order of magnitude.

2. The method for preparing a wide temperature range self-lubricating material according to claim 1, characterized in that: In both step (1) and step (3), the vacuum pressure impregnation is first carried out in an environment with a vacuum degree of 0.08-0.1 MPa for 20-40 min, and then high-pressure nitrogen is introduced, and the pressure is controlled at 0.02 MPa-0.05 MPa and maintained for 30-60 min.

3. The method for preparing a wide temperature range self-lubricating material according to claim 1, characterized in that: In step (2), the hydrothermal reaction is carried out at 180-220° C. for 22-26 hours.

4. The method for preparing a wide temperature range self-lubricating material according to claim 1, characterized in that: In the Ag precursor solution, the solvent is a mixture of water, anhydrous ethanol and pyridine in a volume ratio of (7~4): (2~5): (0~1).

5. The method for preparing a wide temperature range self-lubricating material according to claim 1, characterized in that: In step (4), the hydrothermal reaction is carried out at 170-190° C. for 22-26 hours.

6. A wide temperature range self-lubricating material obtained by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High temperature self compensatiojn lubrication wear resistance material and its preparing method

    CN1275727C

  • VN-AgMoS2 composite material with wide temperature range self-lubricating performance and preparation method of VN-AgMoS2 composite material

    CN111961944A

  • High-entropy alloy-based self-lubricating composite material and preparation method thereof

    CN114101675A